2020
DOI: 10.3389/fcimb.2020.00261
|View full text |Cite
|
Sign up to set email alerts
|

The Glutamate System as a Crucial Regulator of CNS Toxicity and Survival of HIV Reservoirs

Abstract: Glutamate (Glu) is the most abundant excitatory neurotransmitter in the central nervous system (CNS). HIV-1 and viral proteins compromise glutamate synaptic transmission, resulting in poor cell-to-cell signaling and bystander toxicity. In this study, we identified that myeloid HIV-1-brain reservoirs survive in Glu and glutamine (Gln) as a major source of energy. Thus, we found a link between synaptic compromise, metabolomics of viral reservoirs, and viral persistence. In the current manuscript we will discuss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 278 publications
(401 reference statements)
1
31
0
Order By: Relevance
“…Glutamate is the main neurotransmitter involved in cognitive functions in the frontal cortex and hippocampus. In previous research, the levels of glutamate were found to be decreased with other viral infections of the CNS, such as HIV-related dementia [8] which has been associated with metabolic derangement [9] . Congruently, Crunfli et al have suggested that the redeployment of metabolism in SARS-CoV-2-infected astrocytes may be associated with a disruption within the glutamatergic pathway.…”
Section: Discussionmentioning
confidence: 92%
“…Glutamate is the main neurotransmitter involved in cognitive functions in the frontal cortex and hippocampus. In previous research, the levels of glutamate were found to be decreased with other viral infections of the CNS, such as HIV-related dementia [8] which has been associated with metabolic derangement [9] . Congruently, Crunfli et al have suggested that the redeployment of metabolism in SARS-CoV-2-infected astrocytes may be associated with a disruption within the glutamatergic pathway.…”
Section: Discussionmentioning
confidence: 92%
“…Dysregulated inhibitory circuits may also lead to abnormal excitatory neurotransmission via the glutamate system, which has long been reported in HAND patients and models [ 64 ]. However, clinical studies of brain glutamate levels in HAND have reported conflicting results, which likely reflects the underlying complexity of HAND in different patients [ 64 ].…”
Section: Neuroimaging and Neuropathological Studies In Hand Patientsmentioning
confidence: 99%
“…Dysregulated inhibitory circuits may also lead to abnormal excitatory neurotransmission via the glutamate system, which has long been reported in HAND patients and models [ 64 ]. However, clinical studies of brain glutamate levels in HAND have reported conflicting results, which likely reflects the underlying complexity of HAND in different patients [ 64 ]. While there is evidence that ART can decrease extracellular glutamate levels in the brain [ 65 ], many studies in model systems have demonstrated that HIV proteins may directly and indirectly enhance glutamatergic signaling [ 66 , 67 ].…”
Section: Neuroimaging and Neuropathological Studies In Hand Patientsmentioning
confidence: 99%
“…An increase in the level of extracellular glutamate, which is considered to be one of the major causes of neuronal toxicity in HIV-1 patients ( Gorska & Eugenin, 2020 ). To assess whether alterations in glutamate levels are critical for the astrocyte-mediated neuronal damage, and to deduce whether the increase in the level of extracellular glutamate has any effects on neuronal death, we performed a TUNEL assay on neurons.…”
Section: Resultsmentioning
confidence: 99%